ANALISIS FAKTOR RISIKO KEJADIAN OBESITAS SENTRAL PADA IBU RUMAH TANGGA DI PERUMAHAN GRIYA LABUAN ASRI DESA SUKAMAJU KECAMATAN LABUAN KABUPATEN PANDEGLANG BANTEN TAHUN 2016 - Faridi, Ahmad; Hidayati, Widyaningrum (Prosiding Seminar Nasional Berseri, 2017)
The purpose of this study was to determine the risk factors of central obesity housewives in Griya Asri Sukamaju village Labuan Labuan Pandeglang District of Banten in 2016. This study is an analytic study with case control study design, the sample cases are housewives who suffered central obesity and control samples are housewives who do not have central obesity. The results showed a significant relationship between the age of respondents, physical activity, energy intake, intake of protein and fat intake with central obesity in a row with a value (p-value = 0.021, p-value = 0.039, p-value = 0.000, p value-= 0,006dan p-value = 0.000), bivariate analysis results showed that the value of p = 0.342, it can be said that there is no significant relationship between education level of central obesity. While the bivariate analysis results in a sequence that does not have a relationship value (p-value = 0.649), between the level of knowledge with the occurrence of central obesity in housewives.